From applying panaceas to mastering complexity: Toward adaptive water governance in river basins - Claudia Pahl-Wostl (2018)
The most persistent obstacles for the sustainable management of water resources lie in the realm of water governance. Numerous recommendations often relying on simplistic 'standard' panaceas have been put forward for water governance reform without testing of appropriateness in diverse contexts. Here we present the first comprehensive comparative analysis of complex water governance and management systems in national river basins, compiling insights from 29 basins in developed and developing/emerging countries. To support a generic but contextual diagnostic approach an analytical framework was developed that makes a distinction between water governance regime, regime performance and environmental and socio-economic context. Results provide evidence that polycentric governance regimes characterized by a distribution of power but effective coordination structures have higher performance. This finding is valid for diverse contexts. The results show a weaker and more context dependent influence of legal frameworks on performance. The ability to respond to challenges from climate change is strongly related to polycentric governance and innovative ways for dealing with uncertainty. Furthermore, our results support findings that economic and institutional development often focuses on and leads to fulfilling needs of the human population at the expense of the environment. Rivers in comparatively good condition in countries with poor governance regimes highlight the urgent need to develop effective water governance structures in parallel to economic development. These exploratory analyses provide valuable methodological and conceptual insights and pave the way for follow-up studies to build a comprehensive knowledge base on complex resource governance systems and diverse management practices worldwide. © 2012 Elsevier Ltd.